AR-NGEUNA 4.0 testing: Augmented reality application for Sundanese traditional food - Yulia, Cica (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2023)
The advancement of Augmented Reality (AR) technology has opened up new opportunities in the development of innovative learning tools. In this scientific paper, we conducted a testing of the